Characterization of symptoms in irritable bowel syndrome with mixed bowel habit pattern. Issue 1 (29th August 2013) - Su, A. M.; Shih, W.; Presson, A. P.; Chang, L.
Abstract Background Irritable bowel syndrome (IBS) with mixed bowel habits (IBS‐M) is a heterogeneous subtype with varying symptoms of constipation and diarrhea, and has not been well characterized. We aimed to characterize gastrointestinal (GI) and non‐GI symptoms in IBS‐M patients from a US patient population, and to compare them with IBS with constipation (IBS‐C) and diarrhea (IBS‐D). Methods Subjects answering community advertisements and meeting Rome III criteria for IBS completed symptom questionnaires. Key Results Of the initial 289 IBS patients identified, one third (n = 51, 32.5%) who met Rome III criteria for IBS‐M endorsed having either loose stools or hard stools due to medication. These patients had more severe symptoms and longer duration of flares compared to the rest of the IBS‐M group (p = 0.014, p = 0.005). Excluding IBS‐M patients with medication‐related extremes in stool form who could not be reclassified by medical history, 247 IBS patients were assessed. IBS‐M was the most common (44.1%), followed by IBS‐C (27.9%), IBS‐D (26.3%), and IBS‐U (unsubtyped, 1.6%). While IBS‐M shared symptoms with both IBS‐C and IBS‐D, there were significant differences in the prevalence of bowel habit symptoms (p‐value range: <0.001–0.002). IBS‐M patients reported most bothersome symptoms that were more similar to IBS‐D, with the most common being irregular bowel habits (27.5%), bloating (26.6%), and abdominal pain (20.2%). There were no differences in non‐GI symptoms between subtypes. Conclusions & Inferences IBS‐M is a heterogeneous symptom group and thus requires that subclassification criteria be better defined. Use of laxative/antidiarrheal medications adds to the diagnostic complexity in a potentially more severe subset of IBS‐M and should be assessed for accurate subclassification.